Frequencies of the LILRA3 6.7-kb Deletion Are Highly Differentiated Among Han Chinese Subpopulations and Involved in Ankylosing Spondylitis Predisposition - Wang, Han; Wang, Yuxuan; Tang, Yundi; Ye, Hua; Zhang, Xuewu; Zhou, Gengmin; Lv, Jiyang; Cai, Yongjiang; Li, Zhanguo; Guo, Jianping; Wang, Qingwen (Frontiers in Genetics, 2019)
Introduction: Leukocyte immunoglobulin-like receptor A3 (LILRA3) belongs to the LILR family with unique feature of a 6.7-kb deletion variation among individuals. Frequencies of the 6.7-kb deletion vary widely across populations, but so far it has not been carefully investigated among Han Chinese subpopulations. Furthermore, we previously identified the non-deleted (functional) LILRA3 as a novel genetic risk for multiple autoimmune diseases. The current study aimed to investigate i) whether frequencies of the LILRA3 6.7-kb deletion differ within Han Chinese subpopulations. ii) whether the functional LILRA3 is a novel genetic risk for ankylosing spondylitis (AS). Methods: The LILRA3 6.7-kb deletion was genotyped in two independent cohorts, including 1567 subjects from Shenzhen Hospital and 2507 subjects from People's Hospital of Peking University. Frequencies of the 6.7-kb deletion were first investigated in combined healthy cohort according to the Chinese administrative district divisions. Association analyses were performed on whole dataset and subsets according to the geographic regions. Impact of the functional LILRA3 on AS disease activity was evaluated. Results: Frequencies of LILRA3 6.7-kb deletion were highly differentiated within Han Chinese subpopulations, being gradually decreased from Northeast (80.6%) to South (47.4%). Functional LILRA3 seemed to be a strong genetic risk in susceptibility to AS under almost all the alternative genetic models, if the study subjects were not geographically stratified. However, stratification analysis revealed that the functional LILRA3 was consistently associated with AS susceptibility mainly in Northern Han subgroup under the alternative genetic models, but not in Central and Southern Hans. Functional LILRA3 conferred an increased disease activity in AS patients (P < 0.0001 both for CRP and ESR, and P = 0.003 for BASDAI). Conclusions: The present study is the first to report that the frequencies of LILRA3 6.7-kb deletion vary among Chinese Hans across geographic regions. The functional LILRA3 is associated with AS susceptibility mainly in Northern Han, but not in Central and Southern Han subgroups. Our finding provides new evidence that LILRA3 is a common genetic risk for multiple autoimmune diseases and highlights the genetic differentiation among different ethnicities, even within the subpopulations of an ethnic group.